Regionalism and Contemporary Artists in Maine: Opportunities and Challenges - Kinghorn, George (Maine Policy Review, 2015)
George Kinghorn, executive director and curator of the University of Maine Museum of Art, discusses the notion of Maine’s regionalism and the challenges and opportunities of sustaining a career as a contemporary artist in Maine with three artists (Lauren Fensterstock, Philip Frey, and Anna Hepler) and a curator (Suzette McAvoy).